-4(5x-7)=3(4x+5)

Simple and best practice solution for -4(5x-7)=3(4x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(5x-7)=3(4x+5) equation:


Simplifying
-4(5x + -7) = 3(4x + 5)

Reorder the terms:
-4(-7 + 5x) = 3(4x + 5)
(-7 * -4 + 5x * -4) = 3(4x + 5)
(28 + -20x) = 3(4x + 5)

Reorder the terms:
28 + -20x = 3(5 + 4x)
28 + -20x = (5 * 3 + 4x * 3)
28 + -20x = (15 + 12x)

Solving
28 + -20x = 15 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
28 + -20x + -12x = 15 + 12x + -12x

Combine like terms: -20x + -12x = -32x
28 + -32x = 15 + 12x + -12x

Combine like terms: 12x + -12x = 0
28 + -32x = 15 + 0
28 + -32x = 15

Add '-28' to each side of the equation.
28 + -28 + -32x = 15 + -28

Combine like terms: 28 + -28 = 0
0 + -32x = 15 + -28
-32x = 15 + -28

Combine like terms: 15 + -28 = -13
-32x = -13

Divide each side by '-32'.
x = 0.40625

Simplifying
x = 0.40625

See similar equations:

| (6-2w)-(4w+w)+1= | | -1.5+k=8.2 | | 3x-5=x-1 | | x(x+8)-12(x+8)=0 | | 5k^2-2k-7=0 | | 3x-4y+2y=11 | | (-x)(-y)=-xy | | 5p+18=6(p+8) | | 35x+3=28x+2 | | 4b-7=-10b | | 18x^5+15x^4z-75x^3z^2=0 | | 4m+-24= | | 23=3y-(-5) | | (2w+3)+(2w+w)= | | 12+5v=2v | | 15-7x-2x^2=0 | | 3(64x)=2(6x+9) | | 1-10k=-309 | | 2x+2-x+2=1 | | ln(x)-ln(3)=17 | | 1-5k=-309 | | -20=2v-6v | | 8-3(4x-2)+5x=35 | | 28-3(2w+1)=5w-3(5+w) | | 4x^2-1x-14=0 | | 18e=-219 | | 5b+11=7-6b | | X+8+2x=20 | | 13-2x=26 | | 2x-2-4x=6 | | 3.5s-42=4t | | 1=2a+1 |

Equations solver categories